Os Códigos Penais brasileiros no combate à corrupção - Biason, Rita de Cássia (Revista USP, 2022)
Understanding corruption practices in Brazil, from Independence to Operação Lava Jato, implies bringing to light the legal framework pertinent to the control of misappropriation of public resources and abuse of political power. The history of the fight against corruption in Brazil is marked by a punitive-legalistic tradition, since the enactment of the first Penal Code in 1830. In this article, we will analyze how corruption and its other variants were dealt with in the Constitutions of 1822 and 1988 and in the Penal Codes enacted from 1890 to 1940. In the meantime, the crimes of corruption (passive and active), prevarication, concussion, and embezzlement, recurrent practices in the history of Brazilian corruption, are highlighted.